Mother’s Babyface and Children’s Happiness: The Dual Mediating Effects of Self-Efficacy and Resilience (Medico Legal Update, 2019)
Background/Objectives: The purpose of this study was to analyze the dual mediating effects of self-efficacyand resilience in the effects of mother’s babyface on their children’s happiness.Method/Statistical Analysis: Data were collected through surveys. The surveys were conducted for mothersof children attending in elementary and junior high schools. 307 copies were used for the final analysis.SPSS PC + Win. 23 and SPSS PROCESS macro 3.1 were used to analyze descriptive statistics, frequencyanalysis, reliability analysis, correlation analysis, and double mediation effect analysis.Findings: Research findings were as follows. First, there was a significant positive correlation amongmother’s babyface, self-efficacy, resilience, and happiness. Second, the indirect effect of self-efficacy wasverified in the relationship between mother’s babyface, and happiness of children. On the other hand, indirecteffects of resilience did not appear in the relationship between mother’s babyface and children’s happiness.Indirect effects of self-efficacy and resilience on the relationship between mother’s babyface, and children’shappiness were verified.Improvements/Applications: These results can be applied to increase children’s happiness by usingmothers’ variables such as mother’s babyface, self-efficacy and resilience.